The Effect of Electronic Portfolio Assessment Model to Increase of Students’ Generic Science Skills in Practical Inorganic Chemistry - Ramlawati Ramlawati; Liliasari Liliasari; Muhamad Abdulkadir Martoprawiro; Ana Ratna Wulan (Intelektual Pustaka Media Utama, 2014)
Electronic portfolio assessment (EPA) is an assessment procedure based assessment for learning which is a collection of student work collected digitally. The purpose of this research was to determine the effect of implementation of the EPA model to increase students’ generic science skills (GSS) in Practical Inorganic Chemistry. Research was conducted at Chemistry Education Department on preservice teacher programme. The research design was a Pretest-Posttest Control Group Design. Research subjects each consisted of 30 students in the experimental and control Group. Data was collected using GSS test given at pretest and posttest. Data were analyzed by SPSS version 17.0. The result show that students who used EPA model in the assessment process have increased GSS (mean of N-gain= 0.41) better than those used conventional portfolio assessment (mean of N-gain = 0.14).